Formononetin Ameliorates Renal Dysfunction, Oxidative Stress, Inflammation, and Apoptosis and Upregulates Nrf2/HO-1 Signaling in a Rat Model of Gentamicin-Induced Nephrotoxicity - Althunibat, Osama Y.; Abukhalil, Mohammad H.; Aladaileh, Saleem H.; Qaralleh, Haitham; Al-Amarat, Wesam; Alfwuaires, Manal A.; Algefare, Abdulmohsen I.; Namazi, Nader Ibrahim; Melebary, Sahar J.; Babalghith, Ahmad O.; Conte-Junior, Carlos Adam (Frontiers in Pharmacology, 2022)
Gentamicin (GEN) is a bactericidal aminoglycoside known to cause nephrotoxicity. Formononetin (FN) is a potent flavonoid that exhibits numerous promising pharmacological activities. In this study, we have assessed the nephroprotective efficacy of FN against GEN-induced renal injury in rats. Rats were orally administered with FN (60 mg/kg/day, for 2 weeks) and were co-treated with intraperitoneal (i.p.) injection of GEN (100 mg/kg/day) during the days 8–14. GEN-treated rats demonstrated increased urea and creatinine levels in serum associated with marked histopathological changes in the kidney. Malondialdehyde (MDA) and protein carbonyl contents were elevated, whereas glutathione concentration and catalase and superoxide dismutase activities were lowered in GEN-administered rats. The FN largely prevented tissue damage, attenuated renal function, reduced MDA and protein carbonyl, and enhanced antioxidant capacity in the kidney of GEN-administrated animals. The kidney of GEN-treated rats demonstrated elevated Bax and caspase-3 protein expression, accompanied by lowered Bcl-2 protein expression, an effect that FN attenuated. Moreover, FN treatment caused upregulation of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase 1 (HO-1) expression in renal tissue of GEN-intoxicated animals. Collectively, FN protects against GEN-caused renal damage via exhibiting antioxidant, anti-inflammatory, and antiapoptotic activities and augmenting Nrf2 signaling, suggesting FN as a promising agent for preventing drug-induced organ damage.